Corporate Social Responsibility and its Macroeconomic Implications - Robert SOVA; Ion STANCU; Laurenţiu FRĂŢILĂ; Anamaria SOVA (Revista de Management Comparat International)
One of main concern of policy makers is pollution and hence the improvement of the environmental quality. The implementation of environment policies aims at improving life and product quality in order to replace those obtained by high polluting processes by less polluting ones. Countries having more strict environmental regulations are likely to suffer from a significant increase of their production costs. As a consequence these countries become less competitive on the international market and may lose their market share. In this context, an increasing attention was granted to the impact of environment policies on foreign trade. Our purpose in this paper is to investigate whether Corporate social responsibility introduced into Eastern European countries have led or not to a decline of exports towards the European Union (EU), and if so how much? This question is important since it is related to the preoccupation of EU new members to increase their exports and the quality of their products. Our econometric methodology based on recent developments of panel data techniques allow us to control for unobservable heterogeneity and hence to get robust empirical robust. Our results highlight a moderated impact of environmental regulations on foreign trade.